Ulvan-chitosan polyelectrolyte complexes as matrices for enzyme induced biomimetic mineralization. (15th February 2018) - Dash, Mamoni; Samal, Sangram K.; Morelli, Andrea; Bartoli, Cristina; Declercq, Heidi A.; Douglas, Timothy E.L.; Dubruel, Peter; Chiellini, Federica
Graphical abstract: Highlights: The present study aims to investigate the role of enzymatic mineralization on polymeric structures bearing both cationic and anionic groups. Polyelectrolyte complexes of ulvan and chitosan are evaluated as matrices for biomimetic mineralization using ALP. Successful mineralization by ALP is observed which improved cellular activity. Abstract: Polyelectrolyte complexes (PEC) of chitosan and ulvan were fabricated to study alkaline phosphatase (ALP) mediated formation of apatitic minerals. Scaffolds of the PEC were subjected to ALP and successful mineral formation was studied using SEM, Raman and XRD techniques. Investigation of the morphology via SEM shows globular structures of the deposited minerals, which promoted cell attachment, proliferation and extracellular matrix formation. The PEC and their successful calcium phosphate based mineralization offers a greener route of scaffold fabrication towards developing resorbable materials for tissue engineering.